It takes a special type of teacher. An investigation into the capabilities of staff working with disengaged students. Issue 13 (10th November 2022) - Thomas, Jeffrey; Cruickshank, Vaughan; Herrlander Birgerson, Ebba; Reid, Donald; te Riele, Kitty
ABSTRACT: The primary purpose of Flexi schools in Australia is to serve students for whom traditional school has not been a good fit and are largely comprised of students who have disengaged and disconnected from traditional education. The reasons behind disengagement are diverse, but young people in Flexis typically have in common a negative prior experience of school, are more likely to have been affected by poverty, marginalisation, trauma, and to experience poorer mental health than their mainstream school counterparts, subsequently, staff working exclusively with disenfranchised and disengaged young people have a different work experience to the traditional teacher. By surveying school principals in Tasmania, Australia, this study finds that some of the documented characteristics usually associated with being a teacher are particularly valued and required in reengagement programe staff. These include the professional skills to plan for and implement effective teaching and learning, and to create and maintain supportive and safe learning environments, as well as the non-academic capabilities of having strong interpersonal and communication skills, and a willingness to learn. The findings have direct implications for the selection, preparation and professional development of staff working with disengaged young people.